If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -7 = 27x + 3 Reorder the terms: -7 + 12x = 27x + 3 Reorder the terms: -7 + 12x = 3 + 27x Solving -7 + 12x = 3 + 27x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-27x' to each side of the equation. -7 + 12x + -27x = 3 + 27x + -27x Combine like terms: 12x + -27x = -15x -7 + -15x = 3 + 27x + -27x Combine like terms: 27x + -27x = 0 -7 + -15x = 3 + 0 -7 + -15x = 3 Add '7' to each side of the equation. -7 + 7 + -15x = 3 + 7 Combine like terms: -7 + 7 = 0 0 + -15x = 3 + 7 -15x = 3 + 7 Combine like terms: 3 + 7 = 10 -15x = 10 Divide each side by '-15'. x = -0.6666666667 Simplifying x = -0.6666666667
| -1x=13 | | 34a-4(5d+2)=36 | | 235=177-x | | -5n-15n=10 | | 6x-2=4x-(-2x+2) | | J=9(3.14)p | | 3x-3=2x-16 | | -5n-n=10 | | 3x-2=16-x^2 | | 185-u=252 | | 3x+5+6x=15 | | 14x+7-2=7 | | 11(y-2)=13(y+4) | | 3p^2+4p=8 | | 11T=8D+12pm | | 4(x+2)+3(2x-5)=31 | | (4x-25)+(3x-75)=180 | | 3-k=14 | | 6(4)+-25=7+-2(4) | | (8x+25)+(3x+75)=180 | | (2x-7)-(x-6)=14 | | 3x-3-24=4x-4 | | 2x-11=3x-7 | | y=16x+16+19 | | 1x-9=-27 | | 2+2=m | | 4x+7-7x=14 | | 2x+8=x-20 | | 9(y+3)=12(y+5) | | -6=7+x | | 12x^2-12x^3= | | 1.5y-0.2y= |